Initial Validation of a Math Progress Monitoring Measure for Prekindergarten Students. (30th May 2020) - Assel, Mike A.; Montroy, Janelle J.; Williams, Jeffrey M.; Foster, Matt; Landry, Susan H.; Zucker, Tricia; Crawford, April; Hyatt, Hannah; Bhavsar, Vibhuti
Given the importance of math in today's society, it is critical that children who are at risk for math difficulty are identified early. We developed and validated a prekindergarten math subtest (i.e., CIRCLE Progress Monitoring [CPM] Math Subtest). This teacher-completed measure evaluates domains considered important for later math development. Evaluation of validity was undertaken in a longitudinal sample of 383 children ( M age = 4.9 years), and a follow-up sample of 3, 691 children ( M age = 4.4 years). The measure demonstrated adequate psychometric properties, including strong internal consistency reliability (α = .94) and test–retest reliability ( r = .78). Evaluation of concurrent and predictive validity demonstrated scores on the CPM Math Subtest were correlated with scores on other assessments at high levels ( r s from .55–.65). Exploratory and confirmatory factor analyses revealed that the subtest conforms to a well-defined five-factor model that parallels areas considered to be important in the math literature.